Mycobacterium tuberculosis induces delayed lipid droplet accumulation in dendritic cells depending on bacterial viability and virulence. Issue 2 (16th January 2023) - Costa, Maria Fernanda de Souza; Pereira‐Dutra, Filipe; Deboosere, Nathalie; Jouny, Samuel; Song, Ok‐Ryul; Iack, Guilherme; Souza, Andreia Lamoglia; Roma, Eric Henrique; Delorme, Vincent; Bozza, Patricia T.; Brodin, Priscille
Abstract: Tuberculosis remains a global health threat with high morbidity. Dendritic cells (DCs) participate in the acute and chronic inflammatory responses to Mycobacterium tuberculosis (Mtb) by directing the adaptive immune response and are present in lung granulomas. In macrophages, the interaction of lipid droplets (LDs) with mycobacteria‐containing phagosomes is central to host‐pathogen interactions. However, the data available for DCs are still a matter of debate. Here, we reported that bone marrow‐derived DCs (BMDCs) were susceptible to Mtb infection and replication at similar rate to macrophages. Unlike macrophages, the analysis of gene expression showed that Mtb infection induced a delayed increase in lipid droplet‐related genes and proinflammatory response. Hence, LD accumulation has been observed by high‐content imaging in late periods. Infection of BMDCs with killed H37Rv demonstrated that LD accumulation depends on Mtb viability. Moreover, infection with the attenuated strains H37Ra and Mycobacterium bovis ‐BCG induced only an early transient increase in LDs, whereas virulent Mtb also induced delayed LD accumulation. In addition, infection with the BCG strain with the reintroduced virulence RD1 locus induced higher LD accumulation and bacterial replication when compared to parental BCG. Collectively, our data suggest that delayed LD accumulation in DCs is dependent on mycobacterial viability and virulence. Abstract : Mycobacterium tuberculosis replicate inside BMDCs and induce LD accumulation, which is related to RD1 locus, strain virulence and bacterial viability.